A combined image-modelling approach assessing the impact of hyperinflation due to emphysema on regional ventilation–perfusion matching. Issue 2 (4th March 2017) - Burrowes, K.S.; Doel, T.; Kim, M.; Vargas, C.; Roca, J.; Grau, V.; Kay, D.
Abstract : Chronic obstructive pulmonary disease (COPD) is a leading cause of death worldwide. The disease is characterised by airways remodelling and emphysema, which leads to airflow limitation and reduces ventilation–perfusion matching resulting in diminished gas exchange. Emphysematous regions of lung have been shown to have reduced ventilation. Here, we present a combined imaging-modelling study to characterise the impact of emphysema on ventilation and the resultant ventilation–perfusion matching and oxygen exchange. We have constructed patient-based models of five COPD subjects and one healthy control from high-resolution CT data. We present a novel method for extracting definitions of the pulmonary segments using a combined image-modelling approach. The functional models include patient-based geometry and integration of patient-based tissue density from CT into the ventilation model. The mechanism through which we have included the impact of emphysema is via hyperinflation; emphysematous tissue is more expanded and therefore less compliant. This results in diminished ventilation in regions with low tissue density. We have found that segments with the most severe emphysema (with a maximum of 40% of tissue having emphysema) had up to a 400% decrease in ventilation. The diverted ventilation ended up in segments with less or no emphysema ( < ∼15%). Predictions of arterial oxygen partial pressure were found to correlate well with measured values of post-bronchodilator FEV1 . This study presents a combined image-modelling approach that predicts a reduction in regional ventilation due to emphysema which has been shown to occur via functional imaging studies.